Competition for a Prize - Rob van der Noll (Tinbergen Institute, 2006)
I present a model in which individuals compete for a prize by choosing to apply or not. Abilities are private information and in attempt to select the best candidate, the committee compares applicants with an imperfect technology. The choice of application cost, size of the prize and use of information technology are being characterized. In equilibrium, the number of applicants is stochastic and may overload the committee. I show that in spite of overload, the optimal cost (size of the prize) is decreasing (increasing) in market size. Furthermore I show when having a perfect information technology is not optimal.
Keywords: D82; 330; asymmetric information; beauty contest design; award competition; information overload